Lack of Chemopreventive Activity of Agaricus blazei Mushroom on the Development of 1,2-Dimethylhydrazine-Induced Colonic Aberrant Crypt Foci in Rats - Ribeiro-Santos, Giovanna [UNESP]; Barbisan, Luis Fernando [UNESP]; Lopes, Fabiane Catanho [UNESP]; Tozzi Spinardi-Barbisan, Ana Lucia [UNESP]; da Eira, Augusto Ferreira [UNESP]; Kaneno, Ramon [UNESP] (Lawrence Erlbaum Assoc Inc-taylor & Francis, 2008)
Chemopreventive and immunomodulatory potential of methanolic (MET) and dichloromethanic (DCl) extracts of Agaricus blazei mushroom were investigated in the postinitiation stage of colon carcinogenesis in male Wistar rats. Animals were initiated with 1,2-dimethylhydrazine (DMH) and treated i.g. with DCl or MET extracts. After 9 wk, animals were sacrificed for evaluation of aberrant crypt foci (ACF) development, crypt cellular proliferation, preneoplastic liver lesions (GST-P), proliferative response of spleen cells to mitogen, and natural killer activity. Administration of DCl extracts did not suppress DMH-induced colonic ACF nor did it affect the crypt multiplicity, but the highest dose of MET significantly reduced the development of preneoplastic lesions in the colon and liver. Lymphoproliferative response was slightly decreased in the initiated control group, which was restored by treatment with MET. No toxicity from DCl and MET extracts was observed (groups MET and DCl).